Carbon fiber modified PBT composite material and preparation method thereof
By cleaning and plasma activation of carbon fibers, and soaking with coupling agent solution, the problem of poor compatibility between carbon fibers and PBT resin matrix is solved, and the mechanical properties and anti-static properties of the composite material are significantly improved.
Patent Information
- Application Number
- CN202411990103.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-25
AI Technical Summary
The poor compatibility of existing carbon fibers with PBT resin matrix leads to insufficient mechanical properties and antistatic properties of PBT materials.
By cleaning and plasma activation of carbon fibers, the surfactivity and chemical activity are improved, and then soaked with a coupling agent solution to form a layer of coupling agent coating, thereby improving the compatibility of carbon fibers with PBT.
The mechanical properties and antistatic properties of carbon fiber modified PBT composite materials have been significantly improved, the compatibility of materials has been improved, and its application performance in structural parts has been improved.
Smart Images

Figure CN119684760A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to a carbon fiber modified PBT composite material and a preparation method thereof. Background Art
[0002] Polybutylene terephthalate (PBT) has the advantages of good wear resistance, mechanical properties, high temperature resistance, etc., and is widely used in switches, electrical equipment, automotive industry and other fields. However, PBT has high resistance, and friction during use will generate static electricity accumulation, which makes the devices made of PBT easy to absorb dust layers and even cause electric sparks. At the same time, when PBT is used as a structural part to replace metal, its mechanical strength cannot meet the requirements of the structural part. Therefore, when PBT is used as a structural part to replace metal, it is necessary to enhance the mechanical properties of PBT and perform antistatic treatment.
[0003] As a new type of inorganic material, carbon fiber has a series of excellent properties such as high specific strength, high specific modulus, and high temperature resistance. It is widely used as a reinforcement for advanced composite materials. At the same time, carbon fiber also has excellent electrical conductivity and can significantly improve the problem of poor antistatic performance of polymers. However, carbon fiber has low surface energy, few active functional groups, and a chemically inert surface, which results in poor compatibility with the resin matrix. Improving the surface energy of carbon fiber is of great help in improving the antistatic and mechanical properties of PBT resin.
[0004] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a carbon fiber modified PBT composite material and a preparation method thereof, aiming to solve the technical problem of poor compatibility between the existing carbon fiber and the PBT resin matrix.
[0006] The technical solution adopted by the present invention to solve the above technical problems is as follows:
[0007] In one aspect, the present invention provides a method for preparing a carbon fiber modified PBT composite material, comprising the steps of:
[0008] Providing cleaned carbon fibers, and subjecting the carbon fibers to plasma activation treatment to obtain activated carbon fibers;
[0009] The activated carbon fiber is soaked in a coupling agent solution, and after drying, a carbon fiber material for PBT modification is obtained;
[0010] Dissolving PBT in a formic acid solvent to obtain a first solution, then adding the carbon fiber for PBT modification to the first solution, stirring for reaction, and then centrifuging to obtain a solid product;
[0011] The solid product is washed with ethanol to obtain a carbon fiber modified PBT composite material.
[0012] The method for preparing the carbon fiber modified PBT composite material comprises the following steps: using distilled acetone to clean the carbon fiber; and the cleaning time is 30-40 hours.
[0013] The method for preparing the carbon fiber modified PBT composite material, wherein the step of subjecting the carbon fiber to plasma activation treatment to obtain activated carbon fiber comprises:
[0014] The carbon fiber is placed in a plasma reaction chamber, and argon gas is introduced at a gas flow rate of 1.5L / min-2.0L / min. Thereafter, oxygen gas is introduced at a gas flow rate of 10mL / min-15mL / min, and a discharge treatment is performed to obtain the activated carbon fiber.
[0015] The method for preparing the carbon fiber modified PBT composite material, wherein the power of the discharge treatment is 60-80W, and the time of the discharge treatment is 80-100s.
[0016] The method for preparing the carbon fiber modified PBT composite material, wherein the coupling agent is selected from one or more of a phthalate coupling agent, an aluminate coupling agent, a silane coupling agent, and a borate coupling agent.
[0017] The method for preparing the carbon fiber modified PBT composite material, wherein the temperature of the drying treatment is 80-120°C.
[0018] The method for preparing the carbon fiber modified PBT composite material, wherein the added amount of the carbon fiber material for PBT modification is 1-50% of the mass of the PBT material.
[0019] On the other hand, the present invention provides a carbon fiber modified PBT composite material, which is prepared by the above-mentioned preparation method of the carbon fiber modified PBT composite material.
[0020] The carbon fiber modified PBT composite material, wherein the surface resistance of the carbon fiber modified PBT composite material is 1.3×10 7 -1.6×10 9 Ω.
[0021] The carbon fiber modified PBT composite material has a tensile strength of 103-183 MPa, a flexural modulus of 5653-12584 MPa, and a flexural strength of 158-264 MPa.
[0022] Beneficial effects: The carbon fiber modified PBT composite material prepared in the present invention can, on the one hand, improve the problem of poor compatibility between existing PBT materials and carbon fibers, and on the other hand, the mechanical properties and antistatic properties of the prepared composite material are improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0024] Figure 1 The present invention is a schematic diagram of a process for preparing a carbon fiber modified PBT composite material. DETAILED DESCRIPTION
[0025] The present invention provides a carbon fiber modified PBT composite material and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0026] First, as Figure 1 As shown, the present invention provides a method for preparing a carbon fiber modified PBT composite material, characterized in that it comprises the steps of:
[0027] S1, providing a cleaned carbon fiber, and performing a plasma activation treatment on the carbon fiber to obtain an activated carbon fiber;
[0028] S2, soaking the activated carbon fiber in a coupling agent solution, and obtaining a carbon fiber material for PBT modification after drying;
[0029] S3, dissolving PBT in a formic acid solvent to obtain a first solution, then adding carbon fiber to the first solution, stirring for reaction, and then centrifuging to obtain a solid product;
[0030] S4. The solid product is washed with ethanol to obtain a carbon fiber modified PBT composite material.
[0031] It should be noted that carbon fiber, as a new type of lightweight and high-strength material, has attracted much attention in the fields of aerospace, automobile manufacturing, etc. in recent years. In order to further improve its performance and extend its service life, a special coating is usually applied to the surface of the carbon fiber. Among them, epoxy resin is widely used in the surface protection of carbon fiber because of its strong adhesion, corrosion resistance and wear resistance. At the same time, it can effectively isolate the external environment from direct contact with the carbon fiber.
[0032] Based on the fact that the carbon fiber used is usually a carbon fiber with an epoxy resin coating, in the present invention, the carbon fiber is first cleaned to remove the epoxy resin coating on the surface of the carbon fiber, which is beneficial to the subsequent surface treatment of the carbon fiber, and avoids the performance of the prepared carbon fiber material for PBT modification being affected by the presence of the epoxy resin coating. Thereafter, the cleaned carbon fiber is subjected to plasma activation treatment, that is, the cleaned carbon fiber is placed in a plasma reaction chamber, and the surface of the carbon fiber is modified by high-energy plasma to obtain activated carbon fiber. On the one hand, the plasma surface treatment can improve the hydrophilicity of the carbon fiber surface and enhance its bonding with the matrix material. On the other hand, the plasma surface treatment can change the chemical properties of the carbon fiber surface and increase the activity of the surface chemical reaction. In addition, the plasma surface treatment can also introduce surface active groups to improve the chemical activity of the carbon fiber surface, which is beneficial to the chemical bond with the PBT matrix, thereby improving the bonding strength between the modified carbon fiber and the PBT matrix.
[0033] Furthermore, in the present invention, by immersing the activated carbon fiber in a coupling agent solution, a layer of coupling agent coating can be formed on the surface of the activated carbon fiber, thereby effectively improving the surface activity of the carbon fiber and obtaining a carbon fiber material for PBT modification.
[0034] In the present invention, the method for surface modification of carbon fiber adopted is relatively simple, and the carbon fiber main body structure can be relatively completely kept from being damaged during the modification process, and because the surface of the carbon fiber is fully modified, the prepared carbon fiber material for PBT modification has good compatibility in the PBT matrix material, and at the same time, when the prepared carbon fiber material for PBT modification is mixed with the PBT matrix material to prepare a composite material, the original mechanical properties and poor antistatic properties of the PBT matrix material can be effectively improved, so that the prepared composite material has excellent mechanical properties and antistatic properties. In addition, the method for surface modification of carbon fiber of the present invention also has the advantages of low cost, short preparation cycle, green environmental protection, etc., which is conducive to large-scale promotion in industry.
[0035] Furthermore, in the present invention, when the prepared carbon fiber material for PBT modification is mixed with a PBT matrix material to prepare a composite material, the original poor mechanical properties and antistatic properties of the PBT matrix material can be effectively improved, so that the prepared composite material has excellent mechanical properties and antistatic properties.
[0036] In the present invention, the PBT matrix material can be a common commercially available PBT resin, or a mixture of multiple PBTs with different melting temperatures, that is, the PBT matrix material can include 50-90 parts of a common commercially available PBT resin and 10-50 parts of a low-melting-point PBT resin, wherein the melting temperature of the low-melting-point PBT resin is 100-200°C, and the melting temperature of the common commercially available PBT resin is 250-300°C.
[0037] In some embodiments, in step S1, the carbon fibers are cleaned with distilled acetone; the cleaning time is 30-40 hours.
[0038] Specifically, in the present invention, the carbon fiber to be cleaned can be placed in a Soxhlet extractor, and acetone is used as an organic solvent, which is heated to 75-85°C, so that the acetone is continuously evaporated and condensed in the Soxhlet extractor, that is, the carbon fiber is continuously cleaned in the distilled acetone, and the cleaning time is 30-40 hours to ensure that the epoxy resin coating on the surface of the carbon fiber is completely removed. Thereafter, the carbon fiber is taken out and dried in an oven at 80-90°C for 4-6 hours to avoid drying in subsequent processes.
[0039] In some embodiments, in step S1, the carbon fiber is subjected to plasma activation treatment to obtain activated carbon fiber, including: placing the carbon fiber in a plasma reaction chamber, introducing argon gas with a gas flow rate of 1.5L / min-2.0L / min, and then introducing oxygen gas with a gas flow rate of 10mL / min-15mL / min, and performing a discharge treatment to obtain activated carbon fiber;
[0040] In the present invention, the cleaned carbon fiber is placed in a plasma reaction chamber, and the surface of the carbon fiber is modified by high-energy plasma. On the one hand, the plasma surface treatment can improve the hydrophilicity of the carbon fiber surface and enhance its bonding force with the matrix material. On the other hand, the plasma surface treatment can change the chemical properties of the carbon fiber surface and increase the activity of the surface chemical reaction. In addition, the plasma surface treatment can also introduce surface active groups, thereby improving the chemical activity of the carbon fiber surface.
[0041] In some embodiments, the power of the discharge treatment is 60-80 W, and the time of the discharge treatment is 80-100 s.
[0042] Specifically, the power of the discharge treatment can be 60 W, 70 W, 80 W or any value within the range of 60-80 W, and the discharge treatment time can be 80 s, 90 s, 100 s or any value within the range of 80-100 s.
[0043] It should be noted that, in the present invention, the surface depth of the carbon fiber treated by plasma activation can be made not more than 100 μm, so that the main structure of the carbon fiber will not be damaged, and the strength of the carbon fiber body will not be damaged. Specifically, the carbon fiber used in the present invention can be a carbon fiber with a diameter of 3 mm, 6 mm or 8 mm.
[0044] In some embodiments, in step S2, the coupling agent is selected from one or more of a phthalate coupling agent, an aluminate coupling agent, a silane coupling agent, and a borate coupling agent.
[0045] In the present invention, the coupling agent, as an interface modifier, can improve the interface performance between the inorganic filler and the resin matrix, so that the inorganic filler can be better dispersed, which has a good effect on improving the mechanical properties of the composite material product.
[0046] In some embodiments, the drying temperature is 80-120°C.
[0047] Specifically, the temperature of the drying process may be 90°C, 100°C, 110°C, 120°C or any value within the range of 90-120°C.
[0048] In some embodiments, the amount of carbon fiber material added for PBT modification is 1-50% of the mass of the PBT material.
[0049] Specifically, the amount of carbon fiber material added for PBT modification can be 1%, 10%, 20%, 30%, 40%, 50% or any value in the range of 1-50% of the mass of the PBT material. Preferably, the amount of carbon fiber material added for PBT modification is 10-40% of the mass of the PBT material. More preferably, the amount of carbon fiber material added for PBT modification is 30-40% of the mass of the PBT material.
[0050] On the other hand, the present invention provides a carbon fiber modified PBT composite material, which is prepared by the above-mentioned preparation method of the carbon fiber modified PBT composite material.
[0051] Specifically, the surface resistance of the prepared carbon fiber modified PBT composite material is 1.3×10 7 -1.6×10 9Ω, the tensile strength of the carbon fiber modified PBT composite material is 103-183 MPa, the flexural modulus is 5653-12584 MPa, and the flexural strength is 158-264 MPa.
[0052] The following is a further explanation of a carbon fiber modified PBT composite material and a preparation method thereof of the present invention through specific examples. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments, and are only used to illustrate the present invention but not to limit the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0053] It should be noted that the experimental methods in the following embodiments are all routine operations unless otherwise specified, and the reagents involved are all obtained through commercial channels unless otherwise specified.
[0054] Example 1
[0055] (1) Cleaning of carbon fiber
[0056] The carbon fiber bundle was placed in a Soxhlet extractor, acetone was used as the solvent, and it was heated to 75°C to allow the acetone to evaporate continuously and condense in the Soxhlet extractor, so that the impurities on the surface of the carbon fiber were continuously cleaned in the distilled acetone for 30 hours; thereafter, the carbon fiber was taken out and dried in an oven at 80°C for 4 hours.
[0057] (2) Preparation of activated carbon fibers
[0058] The carbon fiber was placed in a plasma reaction chamber, and high-purity argon gas with a gas flow rate of 1.5L / min was first introduced for 5 minutes; then, pure oxygen gas with a gas flow rate of 10mL / min was introduced for 5 minutes, and the discharge treatment was performed at a power of 60W for 80s to prepare activated carbon fiber.
[0059] (3) Preparation of carbon fiber materials for PBT modification
[0060] The activated carbon fiber was immersed in NXT-105 titanate coupling agent solution and dried at 100°C to obtain a carbon fiber material for PBT modification. (4) Preparation of composite materials 10 g of PBT material was dissolved in formic acid solution to obtain a PBT solution. Thereafter, 1 g of carbon fiber material for PBT modification was added to the PBT solution and stirred for reaction for 2 h. Thereafter, the reaction product was centrifuged to obtain a solid product. The solid product was washed with ethanol and dried to obtain a composite material.
[0061] Example 2
[0062] (1) Cleaning of carbon fiber
[0063] The carbon fiber bundle was placed in a Soxhlet extractor, acetone was used as the solvent, and it was heated to 80°C so that the acetone was continuously evaporated and condensed in the Soxhlet extractor, so that the impurities on the surface of the carbon fiber were continuously cleaned in the distilled acetone for 35 hours; thereafter, the carbon fiber was taken out and dried in an oven at 80°C for 6 hours.
[0064] (2) Preparation of activated carbon fibers
[0065] The carbon fiber was placed in a plasma reaction chamber, and high-purity argon gas with a gas flow rate of 2L / min was first introduced for 5 minutes; then, pure oxygen gas with a gas flow rate of 15mL / min was introduced for 5 minutes, and the discharge treatment was performed at a power of 70W for 90s to prepare activated carbon fiber.
[0066] (3) Preparation of carbon fiber materials for PBT modification
[0067] The activated carbon fiber was immersed in NXT-105 titanate coupling agent solution and dried at 100° C. to obtain a carbon fiber material for PBT modification.
[0068] (4) Preparation of composite materials
[0069] 10g of PBT material was dissolved in formic acid solution to obtain a PBT solution, and then 2g of carbon fiber material for PBT modification was added to the PBT solution and stirred for reaction for 2h. Then, the reaction product was centrifuged to obtain a solid product, and the solid product was washed with ethanol and dried to obtain a composite material.
[0070] Example 3
[0071] (1) Cleaning of carbon fiber
[0072] The carbon fiber bundle was placed in a Soxhlet extractor, acetone was used as the solvent, and it was heated to 85°C to allow the acetone to evaporate continuously and condense in the Soxhlet extractor, so that the impurities on the surface of the carbon fiber were continuously cleaned in the distilled acetone for 40 hours; thereafter, the carbon fiber was taken out and dried in an oven at 80°C for 6 hours.
[0073] (2) Preparation of activated carbon fibers
[0074] The carbon fiber was placed in a plasma reaction chamber, and high-purity argon gas with a gas flow rate of 2L / min was first introduced for 8 minutes; then, pure oxygen gas with a gas flow rate of 12mL / min was introduced for 7 minutes, and the discharge treatment was performed at a power of 60W for 100s to prepare activated carbon fiber.
[0075] (3) Preparation of carbon fiber material for PBT modification The activated carbon fiber was immersed in NXT-105 titanate coupling agent solution and dried at 100° C. to obtain the carbon fiber material for PBT modification.
[0076] (4) Preparation of composite materials
[0077] 10g of PBT material was dissolved in formic acid solution to obtain a PBT solution, and then 3g of carbon fiber material for PBT modification was added to the PBT solution and stirred for reaction for 2h. Then, the reaction product was centrifuged to obtain a solid product, and the solid product was washed with ethanol and dried to obtain a composite material.
[0078] Example 4
[0079] (1) Cleaning of carbon fiber
[0080] The carbon fiber bundle was placed in a Soxhlet extractor, acetone was used as the solvent, and it was heated to 85°C to allow the acetone to evaporate continuously and condense in the Soxhlet extractor, so that the impurities on the surface of the carbon fiber were continuously cleaned in the distilled acetone for 35 hours; thereafter, the carbon fiber was taken out and dried in an oven at 80°C for 5 hours.
[0081] (2) Preparation of activated carbon fibers
[0082] The carbon fiber was placed in a plasma reaction chamber, and high-purity argon gas with a gas flow rate of 1.8 L / min was first introduced for 5 minutes; then, pure oxygen gas with a gas flow rate of 10 mL / min was introduced for 7 minutes, and the discharge treatment was performed at a power of 65 W for 85 seconds to prepare activated carbon fiber.
[0083] (3) Preparation of carbon fiber materials for PBT modification
[0084] The activated carbon fiber was immersed in NXT-105 titanate coupling agent solution and dried at 100° C. to obtain a carbon fiber material for PBT modification.
[0085] (4) Preparation of composite materials
[0086] 10 g of PBT material was dissolved in formic acid solution to obtain a PBT solution, and then 4 g of carbon fiber material for PBT modification was added to the PBT solution and stirred for reaction for 2 h. Then, the reaction product was centrifuged to obtain a solid product, and the solid product was washed with ethanol and dried to obtain a composite material.
[0087] Example 5
[0088] (1) Cleaning of carbon fiber
[0089] The carbon fiber bundle was placed in a Soxhlet extractor, acetone was used as the solvent, and it was heated to 85°C to allow the acetone to evaporate continuously and condense in the Soxhlet extractor, so that the impurities on the surface of the carbon fiber were continuously cleaned in the distilled acetone for 35 hours; thereafter, the carbon fiber was taken out and dried in an oven at 80°C for 5 hours.
[0090] (2) Preparation of activated carbon fibers
[0091] The carbon fiber was placed in a plasma reaction chamber, and high-purity argon gas with a gas flow rate of 2L / min was first introduced for 5 minutes; then, pure oxygen gas with a gas flow rate of 15mL / min was introduced for 7 minutes; the discharge treatment was performed at a power of 70W for 85s to prepare activated carbon fiber.
[0092] (3) Preparation of carbon fiber materials for PBT modification
[0093] The activated carbon fiber was immersed in NXT-105 titanate coupling agent solution and dried at 100°C to obtain the carbon fiber material for PBT modification.
[0094] (4) Preparation of composite materials
[0095] 10 g of PBT material was dissolved in formic acid solution, and then 5 g of carbon fiber material for PBT modification was added to the PBT solution. The reaction was stirred for 2 h, and the reaction product was centrifuged to obtain a solid product. The solid product was washed with ethanol and dried to obtain a composite material.
[0096] Example 6
[0097] (1) Cleaning of carbon fiber
[0098] The carbon fiber bundle was placed in a Soxhlet extractor, acetone was used as the solvent, and it was heated to 85°C to allow the acetone to evaporate continuously and condense in the Soxhlet extractor, so that the impurities on the surface of the carbon fiber were continuously cleaned in the distilled acetone for 35 hours; thereafter, the carbon fiber was taken out and dried in an oven at 80°C for 5 hours.
[0099] (2) Preparation of activated carbon fibers
[0100] The carbon fiber was placed in a plasma reaction chamber, and high-purity argon gas with a gas flow rate of 2L / min was first introduced for 5 minutes; then, pure oxygen gas with a gas flow rate of 15mL / min was introduced for 7 minutes; the discharge treatment was performed at a power of 70W for 85s to prepare activated carbon fiber.
[0101] (3) Preparation of carbon fiber materials for PBT modification
[0102] The activated carbon fiber was immersed in NXT-105 titanate coupling agent solution and dried at 100°C to obtain the carbon fiber material for PBT modification.
[0103] (4) Preparation of composite materials
[0104] 10g of PBT material was dissolved in formic acid solution, and then 0.1g of carbon fiber material for PBT modification was added to the PBT solution. The reaction was stirred for 2h, and the reaction product was centrifuged to obtain a solid product. The solid product was washed with ethanol and dried to obtain a composite material.
[0105] Comparative Example 1
[0106] Unmodified PBT material.
[0107] Comparative Example 2
[0108] 10g of PBT material was dissolved in formic acid solution to obtain a PBT solution, and then 4g of carbon fiber material was added to the PBT solution and stirred for reaction for 2h. Then, the reaction product was centrifuged to obtain a solid product, and the solid product was washed with formic acid solution, ethanol, and dried to obtain a composite material.
[0109] Furthermore, the surface resistance and mechanical properties of the composite materials prepared in Examples 1-6 and Comparative Examples 1-2 were tested in the present application, wherein the products of Examples 1-6 and Comparative Examples 1-2 were injection molded into standard samples using an injection molding machine, and the performance of the standard samples was characterized according to national standards. Among them, the performance test methods are:
[0110] (1) Notched impact strength test: test standard ISO 180;
[0111] (2) Tensile strength test: test standard ISO 527;
[0112] (3) Flexural strength test: test standard ISO 178;
[0113] (4) Flexural modulus test: test standard ISO 178;
[0114] (5) Heat deformation temperature test: test standard ISO 75;
[0115] (6) Surface resistance test: test standard GB / T 1410.
[0116] The results are shown in the following table:
[0117]
[0118] As can be seen from the table, the surface resistance of the carbon fiber modified PBT composite material prepared in this application is significantly reduced, and the antistatic effect of the material is significantly improved. At the same time, the bending modulus and bending strength are significantly improved, the impact strength is significantly improved, and the thermal deformation temperature of the material reaches 196-232°C, which is much higher than the thermal deformation temperature of pure PBT resin at 80°C. This shows that the modified carbon fiber provided by the present invention has excellent compatibility with PBT, which can greatly improve the antistatic performance of PBT and significantly enhance the mechanical properties of PBT.
[0119] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing a carbon fiber modified PBT composite material, characterized in that: Includes steps: Providing cleaned carbon fibers, and subjecting the carbon fibers to plasma activation treatment to obtain activated carbon fibers; The activated carbon fiber is soaked in a coupling agent solution, and after drying, a carbon fiber material for PBT modification is obtained; Dissolving PBT in a formic acid solvent to obtain a first solution, then adding the carbon fiber for PBT modification to the first solution, stirring for reaction, and then centrifuging to obtain a solid product; The solid product is washed with ethanol to obtain a carbon fiber modified PBT composite material.
2. The method for preparing a carbon fiber-modified PBT composite material according to claim 1, characterized in that: The carbon fiber is cleaned with distilled acetone; wherein the cleaning time is 30-40 hours.
3. The method for preparing the carbon fiber modified PBT composite material according to claim 1, characterized in that: The step of subjecting the carbon fiber to plasma activation treatment to obtain activated carbon fiber comprises: The carbon fiber is placed in a plasma reaction chamber, and argon gas is introduced at a gas flow rate of 1.5L / min-2.0L / min. Thereafter, oxygen gas is introduced at a gas flow rate of 10mL / min-15mL / min, and a discharge treatment is performed to obtain the activated carbon fiber.
4. The method for preparing a carbon fiber-modified PBT composite material according to claim 3, characterized in that: The power of the discharge treatment is 60-80W, and the time of the discharge treatment is 80-100s.
5. The method for preparing the carbon fiber modified PBT composite material according to claim 4, characterized in that: The coupling agent is selected from one or more of a phthalate coupling agent, an aluminate coupling agent, a silane coupling agent, and a borate coupling agent.
6. The method for preparing the carbon fiber modified PBT composite material according to claim 5, characterized in that: The temperature of the drying process is 80-120°C.
7. The method for preparing a carbon fiber modified PBT composite material according to claim 1, characterized in that: The added amount of the carbon fiber material for PBT modification is 1-50% of the mass of the PBT material.
8. A carbon fiber modified PBT composite material, characterized in that: The carbon fiber-modified PBT composite material is prepared by the preparation method of any one of claims 1 to 7.
9. The carbon fiber modified PBT composite material according to claim 8, characterized in that: The surface resistance of the carbon fiber modified PBT composite material is 1.3×10 7 -1.6×10 9 Ω.
10. The carbon fiber modified PBT composite material according to claim 9, characterized in that: The carbon fiber modified PBT composite material has a tensile strength of 103-183 MPa, a flexural modulus of 5653-12584 MPa, and a flexural strength of 158-264 MPa.
Citation Information
Patent Citations
Methods of treating carbon fibers, fiber-reinforced resins, and methods of making the fiber-reinforced resins
CN102965928A
High-performance carbon-fiber enhancement polymer alloy and preparation method thereof
CN104845289A
Preparation method of PA66 grafted carbon fibers
CN110863341A
Modification method of reinforced fiber, reinforced fiber and composite material
CN117510118A
High-performance heat-conducting PET composite material and preparation method thereof
CN117659635A